3D simulation model of warp-knitted patterned velvet fabric. Issue 6 (7th November 2016) - Zhang, Aijun; Li, Xinxin; Ma, Pibo; Xiong, Ying; Jiang, Gaoming
Abstract : Purpose: Realistic geometric description is essential for simulating physical properties of warp-knitted velvet fabrics, which are widely used for home-textiles and garments. The purpose of this paper is to provide an approach to the description of patterned piles and propose a customized simulation model to realize highly real-time simulation of warp-knitted velvet fabrics in three dimensions. Design/methodology/approach: Based on knitting technology and structure features, a mathematical model to qualify forming possibility of piles is conducted by assessing underlaps of pattern bars and pile ground bars. When the pile areas and ground areas are classified, a three-dimensional (3D) space coordinate is built, of which the z -axis is divided into equal spaces to form certain multi-layer textured slices. Color and transparency of piles on each textured slice can be computed and generated by mapping to 3D geometrical grid layers with particular mapping relationship. Moreover, piles' deflection and spatial collision are also taken into account to make sure high uniformity with real fabrics. Findings: According to the models built, a simulator special for warp-knitted patterned velvet fabrics is programed via Visual C++ and the models are proven practical and easily implemented by comparing simulated effect of one sample with real fabric. Research limitations/implications: Because of present limited research, 3D simulation of patterned velvet fabrics knitted on double-needle bar Raschel machine as well as 3D shadow effect will be studied in the further research. Practical implications: The paper includes implications for designing patterned velvet products and shows convenience to instantly see finished effect without sampling on machine. Originality/value: This paper fulfills a featured simulation method for warp-knitted patterned velvet fabrics in 3D dimensions for the first time.